Real-world treatment patterns and outcomes among patients with HER2-positive unresectable or metastatic breast cancer in China - Huang, Jiajia; Chen, Limin; Song, Lihua; Tong, Zhongsheng; Sun, Tao; Wang, Xiaojia; Liu, Yi; Wang, Shusen (Frontiers in Oncology, 2025)
BackgroundBreast cancer is now the most commonly diagnosed cancer in the world and the leading cause of cancer mortality in women worldwide. In past few years, anti- human epidermal growth factor receptor-2 (HER2) therapy for metastatic breast cancer (mBC) has rapidly altered in China. This study aimed to describe treatment patterns and outcomes in patients with HER2-positive unresectable or metastatic breast cancer in the real-world setting.MethodsThis multicenter, retrospective analysis evaluated the treatment patterns and the efficacy in newly diagnosed HER2+ mBC patients between Jan 1, 2020 and Aug 31, 2022. Electronic medical records from 5 cancer centers in China were used.ResultsAmong 865 patients, the most common first-line (1L) treatment regimen was dual anti-HER2 blockade monoclonal antibody-based therapy (Dual anti-HER2 mAB: 36.07%), followed by single anti-HER2 blockade mAB-based therapy (Single anti-HER2 mAB: 21.97%) and single Tyrosine Kinase Inhibitor-based therapy (Single TKI: 19.19%). In the second-line (2L), the primary treatment was single TKI regimen (35.45%), followed by TKI+anti-HER2 blockade mAB-based therapy (TKI+anti-HER2 mAB: 16.36%) and single anti-HER2 mAB (15.15%). De novo mBC at initial diagnosis, recurrence post 6 months of (neo)adjuvant treatment, absence of brain metastasis, and younger age, were associated with the choice of dual anti-HER2 mAB regimen in 1L treatment. Conversely, patients receiving anti-HER2 therapy in (neo)adjuvant setting, having brain metastasis, and experiencing a recurrence within 6 months were more likely to receive TKI-based regimen. The median rwPFS of 1L and 2L treatment declined sequentially, with values of 11.04 [95% confidence interval (CI) 10.19–12.03] months and 7.59 (95% CI 6.21–9.20) months, respectively. Longer disease-free interval (DFI) and the choice of dual-anti HER2 regimen in 1L treatment were associated with longer rwPFS.ConclusionThe results of this study provide valuable real-world insight into HER2 positive mBC treatment trends and clinical outcomes, informing subsequent patient management.